Perbandingan Mekanisme Sertifikasi Pruduk Halal Antara Indonesia Dengan Malaysia - Ferdiansyah, Ferdiansyah; Dompak, Timbul (Prosiding, 2024)
The purpose of this study is to explain how Indonesia and Malaysia, two countries that have certified halal products, do so.The Organizational Authority for Halal Assurance (BPJPH) oversees halal certification in Indonesia. LPPOM MUI (Indonesian Ulema Council) handled this task in the past, marking the beginning of a public movement with state support. Its main objective is to protect Muslims from illegal goods. In contrast, JAKIM (Malaysia Islamic Progress Quarter) takes care of it in Malaysia. While both aim to provide Muslims in both countries with access to safe and secure halal, there are significant differences in how these two agencies in two different countries implement halal certification. in food consumption and the smallest amount possible. This study utilizes a library research methodology, using various sources to help clarify the issues at hand. The findings of this study show how the halal certification process in Malaysia and Indonesia is comparable as non-governmental organizations first handled certification before governmental organizations took control. Laboratory testing is one area where the two countries differ; in Indonesia, it is conducted by LPPOM MUI, whereas independent laboratories with accreditation conduct the testing in Malaysia.